Lots of bots - Richards, C. J. (Richards, C. J. Robots rule!, 2015)
"George is thrilled to score his dream internship at Tinker Tech. But he and his best pal, Jackbot, realize that something does not compute when a dangerous new invention threatens Terabyte Heights. As he and his friends search for answers, they uncover secrets about George's past that may change his life forever"--